2005
DOI: 10.1254/jphs.fpj05019x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Etidronate on Aortic Calcification and Bone Metabolism in Calcitoriol-Treated Rats With Subtotal Nephrectomy

Abstract: Abstract. The present study was undertaken to determine the effects of etidronate (ED) on calcitriol-induced aortic calcification and bone metabolism in rats with renal failure. Severe aortic calcification was induced by treatment with calcitriol for 3 weeks in rats in which 5 / 6 of the kidneys were removed (SNx group). Treatment of ED (10 mg / kg) together with calcitriol after subtotal nephrectomy (SNx) significantly inhibited thoracic and abdominal aortic calcification 3 weeks after the operation; however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…21 Accumulating evidence suggests that bisphosphonates also have the potential to induce the regression of atherosclerotic plaques and vascular calcification in experimental studies [22][23][24] and small clinical studies. [14][15][16] They are grouped into 2 classes according to their chemical structure and the molecular mechanism by which they inhibit osteoclast activity.…”
Section: Discussionmentioning
confidence: 99%
“…21 Accumulating evidence suggests that bisphosphonates also have the potential to induce the regression of atherosclerotic plaques and vascular calcification in experimental studies [22][23][24] and small clinical studies. [14][15][16] They are grouped into 2 classes according to their chemical structure and the molecular mechanism by which they inhibit osteoclast activity.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the significantly reduced mineral apposition rates in ibandronate-treated rats observed in our study support this notion. Etidronate and pamidronate have recently been shown to prevent vascular calcification in uremic rats and, concomitantly, to affect bone formation and mineralization [10,11]. Although a comparison of these studies, including the present one, is hampered by different experimental designs (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Beyond this, individual bisphosphonates of either class differ with respect to the biological half-life, route of administration, side effects, and relative potencies to inhibit bone resorption and formation [7]. In this context it is worth mentioning that a recent study in experimental chronic uremia revealed that the etidronate dosage required to prevent arterial calcification also impaired bone mineralization [10]. In a more recent animal study, etidronate and pamidronate were shown to attenuate ectopic calcification and to reduce bone formation while leaving bone resorption virtually unaffected [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In rodents with renal failure and severe medial calcification, which was induced by 5/6 nephrectomy and treatment with high doses of calcitriol [40,41], etidronate inhibited aortic calcification at a dose (5 mg/kg) but did not significantly affect bone metabolism; consequently, the effects of etidronate on aortic calcification are unrelated to its effects on bone formation and serum calcium levels. …”
Section: Bisphosphonatesmentioning
confidence: 99%